Trust Model for the Russian Federation Digital Economy - Dmitry A. Melnikov; Yury F. Releev; Leonid D. Kvaratskheliya (Безопасность информационных технологий, 2020)
The paper presents a study of modern trust models based on the Public Key Infrastructure (PKI) infrastructure, the purpose of which is to develop a Russian national trust model. To meet this goal, the necessity of creating a national infrastructure of trust in the transition to a digital economy was substantiated. At the same time, the analysis of the current state of the Russian PKI, which is characterized by the absence of a unified structure of the certification authorities (CA) and a unified federal regulatory authority in the field of cryptographic key management (public key certificates), is carried out. An analysis of foreign PKI models of trust allowed us to conclude that none of these models can be used as reference and implemented in the Russian Federation. The basis of the proposed model is the concept of a distributed system of the validation authorities, which has a hierarchical structure and will allow combining all public and private CAs into a single dynamic system that can meet the most diverse needs of the digital economy and citizens of the Russian Federation to manage information security. The implementation of the trust model developed by the authors will allow, first of all, preventing many cybercrimes and attempts to cause financial and economic damage on the subjects of information interaction.